Between Reconciliation and Justice: Reactualizing As-Sulḥ in Resolving Juvenile Violence within Indonesia’s Legal Pluralism - Tomi Adi Syahputra Nasution; Zulpahmi Lubis (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This study examines the tension between reconciliation and justice in the regulation of assault-related offenses under Indonesian positive criminal law and Islamic criminal law, while critically analyzing the implementation of as-sulḥ in resolving juvenile violence within the Halongonan community of North Padang Lawas. Adopting a socio-legal empirical approach, this research conceptualizes law as a social practice (law in action) and draws on qualitative data from in-depth interviews with community leaders, religious figures, and local residents. Data were analyzed using constant comparative analysis based on three key indicators: voluntariness, power balance, and substantive justice. The findings reveal that although as-sulḥ normatively promotes reconciliation, forgiveness, and the restoration of social relations, its practical application often reflects a tension between reconciliation and justice, manifested in the form of pseudo-reconciliation. Settlements tend to occur under social pressure and unequal power relations, making them formalistic and transactional, and failing to fully embody the principles of al-riḍā’ (consent), ‘adālah (justice), and maṣlaḥah (public interest). In response, this study argues for the reactualization of as-sulḥ through the integration of restorative justice, the principles of maqāṣid al-sharī‘ah, and the national criminal law framework within Indonesia’s plural legal system. Theoretically, it contributes to the discourse on reconciliation and justice in legal pluralism, while practically offering a more just, reflective, and context-sensitive model for resolving juvenile violence.